Sedimentation of pollutantcontaining aggregates during purification of wastewater from coking plants - Yelatontsev, Dmytro; Suprunchuk, Volodymyr; Voloshin, Mykola (Eastern-European Journal of Enterprise Technologies, 2017)
We performed the quantitative description of the process of purification of phenolic wastewater from resinous substances by methods of coagulation, flocculation and adsorption. We carried out the coagulation purification with the use of Al2(OH)5Cl and FeCl3 at a dosage of 50 mg/dm3; we used the cationic Extrafloc P70 at a dosage of 4 mg/dm3 as a flocculant; we used natural alkaline bentonite clay at a dosage of 100 mg/dm3 as the adsorbent. The method of sedimentation analysis established the prevailed radii of pollutant-containing aggregates of the dispersed phase of phenolic wastewater, μm: after coagulation of Al2(OH)5Cl − 30...90, after coagulation of FeCl3 − 33...39, after flocculation of Extrafloc P70 − 60...80, after adsorption by bentonite clay separately − 23...27, after adsorption by bentonite clay with the addition of Extrafloc P70 − 70...90. We showed experimentally that under conditions of the combined application of alkaline bentonite clay at a dosage of 100 mg/dm3 with the addition of Extrafloc P70 at a dosage of 4 mg/dm3, the disperse phase of phenolic waters forms the largest pollutant-containing aggregates, which precipitate at rate of 0.61 mg/s. This provides normative content of resinous substances in purified water − 10 mg/dm3, and reduces duration of the purification process from 20 minutes up to 3 min. The rate of sedimentation of pollutant-containing aggregates formed under application of other methods of purification is an order of magnitude smaller, and is, mg/s: Al2(OH)5Cl at a dosage of 50 mg/dm3 − 0.017; FeCl3 at a dosage of 50 mg/dm3 − 0.024; Extrafloc P70 at a dosage of 4 mg/dm3 − 0.05; bentonite clay at a dosage of 100 mg/dm3 − 0.02. The method of purification of phenolic wastewater by bentonite clay with the addition of Extrafloc P70 makes possible to remove 96 % of resinous substances, therefore we can used it to improve the purification process at coke-chemical enterprises